Human error assessment and reduction for total electrical power failures at container ship under decomposed fuzzy analytical hierarchy process - Akyuz, Emre; Cebi, Selcuk (TAYLOR & FRANCIS LTD, 2026)
Electrical power failures on-board container ships pose a serious safety and dependability risk since they frequently result in propulsion loss, navigation system shutdown and subsequent operational problems. Although the technical reasons of blackout have been thoroughly studied, the contribution of human error in the phases of prevention, diagnosis and recovery has not been sufficiently analysed. To remedy this gap, this article performs systematic human error assessment and reduction framework for total electrical power failures (blackout) using the Decomposed Fuzzy Analytical Hierarchy Process (DF-AHP). The proposed method decomposes the overall failure process into hierarchical decision levels allowing for the systematic evaluation of ship crew errors. The outcomes of the research contribute a structured and data-driven approach for quantifying and reducing human errors in complex maritime systems, thereby supporting the advancement of proactive safety management and compliance with IMO and class society requirements for container vessels.
Keywords: Human error; decomposed fuzzy AHP; HEART; blackout; container ship; QUANTIFICATION; NAVIGATION; Engineering